Aplikasi Space Syntax dalam Membangunkan Prototaip Unit Rumah Terbengkalai - Muhamad, Syafiqah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2023)
An abandoned housing project is a project that is stopped for 3 months without being resumed and after a letter of acceptance is issued. The methods used to solve the problem of these abandoned projects have not been improved by rescue developers in Malaysia. This is because there is the latest technology has not been able to solve the problems that arise against abandoned projects. One of the technologies in question is the application of space syntax. Therefore, the objective of this study is to examine the practice of space syntax application in developing abandoned house unit prototype, identify the main problems of space syntax application in developing abandoned house unit prototype and analyze the strength of relationship between practice and main problems of space syntax application in developing abandoned house unit. This study involved rescue developers around the Klang area with the involvement of 36 respondents. This study uses a quantitative approach by providing online distributed questionnaires and physical encounters. Frequency, descriptive, and crosstabs analyzes were used to achieve the objectives of this study. Therefore, this study can help the developer with some suggestions in developing a prototype of an abandoned house unit with space syntax application.